COSMOGENIC BE-10 AND THE SOLID EARTH: STUDIES IN GEOMAGNETISM, SUBDUCTION ZONE PROCESSES, AND ACTIVE TECTONICS - Morris J.D.; Gosse J.; Brachfeld S.; Tera F. (My University, 2002)
Since the mid-1980s, cosmogenic 10Be, with a 1.5 Myr half-life, has proven to be an extremely useful tool for studies of the solid Earth and surface processes. Measured at very low concentrations using a particle accelerator, 10Be reveals tantalizing clues to the behavior of the Earth's geodynamo, permits "geochemical imaging" of physical and magmatic processes in subduction zones, and provides ages and uplift and incision rates essential for understanding active tectonic processes. This paper emphasizes the utility of atmospheric and in «'¿«-produced 10Be in understanding these solid Earth processes, using igneous and sedimentary rocks, deep-sea and lacustrine sediment, and ice cores as archives. One focus of this contribution is on studies of the geodynamo and subduction zone processes that utilize 10Be produced by galactic cosmic radiation (GCR) in the atmosphere and subsequently adsorbed onto marine sediments. Following the extensive treatment of geomagnetic effects on cosmic radiation by Stormer (1955), Elsasser et al. (1956) recognized that variations in cosmogenic nuclide production rates could be used as proxies for changes in intensity of the Earth's magnetic field. A year earlier, Peters (1955) had also proposed that 10Be may be favorable for recording Cenozoic marine sedimentation rates and other geophysical variations. High-resolution °Be-depth profiles in marine sediments have the potential to evaluate the suggestion of asymmetric sawtooth variation in the geomagnetic field paleointensity and to assess the speculation that Milankovitch variations in Earth's orbital parameters may influence the geodynamo. Globally coherent and systematic co-variations in paleointensity and 10Be concentrations.